Cytochemical analysis and stain development in pollen grains of parental lines and hybrids based on cytoplasmic genetic male sterility system in pigeonpea (Cajanus cajan) - SINGH, F; SINGH, I P; MAJUMDER, N D (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2006–08 to determine viability of pollen grains in cytoplasmic genetic male sterile lines of pigeonpea [Cajanus Cajan (L.) Millsp.]. Poor pollen grain formation and their degeneration in subsequent mitotic cell division were evident in male sterile lines. Application of various specific stains revealed the following: carmine, which is used very often for assessing pollen viability may not be very reliable because it is non-specific nucleus, cytoplasm and other organelles, (ii) iodine + potassium iodide (I2 + KI) stain can precisely distinguish the fertile from sterile pollen grains and can also differentiate pollen grains in terms of chemical composition, and (iii) the mixed stain (carmine + ferrous ammonium sulphate + haematoxyline) is very specific to fertile vs sterile pollen grains and can identify various pollen grains with more precision. Staining technique can also be used to detect the distortions in respiratory mechanism and nucleic acid synthesis. Further, the under sized pollen grains and their frequency significantly varied among the ‘A’, ‘B’, ‘R’ lines and the hybrids synthesized there from.